Personality judgment : a realistic approach to person perception - Funder, David Charles (Academic Press, 1999)
Accuracy in judging personality is important in clinical assessment, applied settings, and everyday life. Personality judgments are important in assessing job candidates, choosing friends, and determining who we can trust and rely on in our personal lives. Thus, the accuracy of those judgments is important to both individuals and organizations. In examining personality judgment, this book takes a sweeping look at the field's history, assumptions, and current research findings. The book explores the construct of traits within the person-situation debate, defends the human judge in the face of t.